Dehydrogenation Adjacent to Carbonyls Using Palladium–Allyl Intermediates - Turlik, Aneta; Chen, Yifeng; Newhouse, Timothy R. (Synlett, 2016)
Palladium–allyl chemistry has historically been used as a means of allylation of nucleophiles, as developed by Tsuji and Trost in the 1970s. Also during this decade, the Saegusa oxidation, the most prominent palladium-catalyzed dehydrogenation reaction, was developed. This Synpacts article provides a historical overview of dehydrogenation adjacent to carbonyls and our recent contribution to this area: palladium–allyl catalyzed dehydrogenation of nitriles and esters.
Keywords: dehydrogenation; oxidation; catalysis; palladium; allyl complexes